2016
DOI: 10.3748/wjg.v22.i40.8940
|View full text |Cite
|
Sign up to set email alerts
|

Ansa pancreatica as a predisposing factor for recurrent acute pancreatitis

Abstract: AIMTo determine the non-biased prevalence and clinical significance of ansa pancreatica in patients with acute pancreatitis using magnetic resonance imaging (MRI).METHODSOur institutional review board approved this cross-sectional study, which consisted of a community-based cohort of 587 consecutive participants in a whole-body health-check program, and 73 subjects with episode of acute pancreatitis (55 patients with a single episode of acute pancreatitis, and 18 patients with recurrent acute pancreatitis). Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Many studies have hypothesized ansa pancreatica as a risk factor for acute pancreatitis [40,41]. This hypothesis is supported by the findings of a recent case-control study which reported a significantly higher risk of recurrent acute pancreatitis in individuals with ansa pancreatica [39]. However, no correlation was found with a single episode of acute pancreatitis.…”
Section: Ansa Pancreatica and Pepmentioning
confidence: 87%
“…Many studies have hypothesized ansa pancreatica as a risk factor for acute pancreatitis [40,41]. This hypothesis is supported by the findings of a recent case-control study which reported a significantly higher risk of recurrent acute pancreatitis in individuals with ansa pancreatica [39]. However, no correlation was found with a single episode of acute pancreatitis.…”
Section: Ansa Pancreatica and Pepmentioning
confidence: 87%
“…Hayashi et al in a retrospective analysis demonstrated ansa pancreatica as a predisposing factor for the onset of recurrent AP. The frequency of ansa pancreatica was highest in patients with alcoholic pancreatitis 2. The exact link between alcohol consumption and ansa pancreatica leading to recurrent AP is unknown.…”
Section: Descriptionmentioning
confidence: 97%
“…21 In the present cadaveric study, ansa pancreatica (type V) was observed in one cadaveric specimen, but not radiologically. It was reported radiologically in the MRCP (1.2%) by Adibelli et al 7 Hayashi et al 22 found that it has a significant association with recurrent acute pancreatitis.…”
mentioning
confidence: 90%